Pengaruh Media Sosial Instagram @Sumbar_Rancak terhadap Pemenuhan Kebutuhan Informasi Wisata Followers - Zahirani, Rifqoh; Nabila, Jeihan (YASIN, 2024)
This research was conducted to determine the influence of social media Instagram @sumbar_rancak on fulfilling followers' tourism information needs. This research consists of two variables, namely the social media variable (X) with indicators of context, communication, collaboration and connection and the information needs variable (Y) with indicators of current need approach, everyday need approach, exhaustic need approach and catching-up need approach. . This research uses a quantitative method by distributing questionnaires to 100 respondents via online media. The population in this study were all Instagram followers @sumbar_rancak. The data analysis techniques used are normality test, correlation test, linearity test, t test, and coefficient of determination test. The aim of this research is to determine the influence of Instagram social media on fulfilling followers' tourism information needs. Based on the results of the coefficient of determination test, it is known that the social media variable (X) has an influence on information needs (Y) of 65.7% while the remaining 34.3% is influenced by other factors not examined in this research. The influence of social media Instagram @sumbar_rancak on followers' tourism information needs is very strong. This can be seen from the results of the correlation test, which is 0.812. Meanwhile, based on the t test, it shows that social media has a positive and significant effect on information needs. This is based on the calculation that tcount 13.795 > ttable 1.984. Then, the research results showed that the social media Instagram @sumbar_rancak was categorized as good so that it gave satisfaction to followers. Meanwhile, followers' information needs for the @sumbar_rancak Instagram account are also categorized as good because they can fulfill followers' information needs well.